Intervertebral disc: regeneration, herniation formation stages and molecular profile (literature review) - Radchenko, Volodymyr; Piontkovsky, Valentyn; Kosterin, Sergey; Dedukh, Ninel (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2018)
Forty sources of scientific literature have been analyzed and information on risk factors, the stage of formation of intervertebral disc herniation, inflammatory cytokines and expression of growth factors are systematized. It is noted that the pain in the lower back is the main reason for the deterioration of patient quality of life and disability. Analysis of the factors of development of intervertebral disc is a relevant task, aimed at preventing the disease. The formation of a hernia is a complex process that runs along the background of violations of the organization of the main structural components of the intervertebral disc (nucleus pulposus, annulus fibrousus, end plates) in conditions of increased stresses, depending on human way of life, genetic heteromorphism of the main macromolecules (collagen and proteoglycans), metabolic disorders indicators on the background of low oxidation of disks, etc. However, there is an alternative view that the formation of hernia does not always precede the degeneration of the annulus fibrousus. Each stage in the formation of a hernia (protrusion, prolapse, extrusion and sequestration) has characteristic histological signs due to a violation of the structural organization of the nucleus and its migration, depending on the ability of the annulus fibrousus and end plates. The nucleus pulposus involved in the inflammatory reaction, producing proinflammatory cytokines and growth factors. The precondition for the degeneration of intervertebral disc with different structural properties may be the polymorphism of genes encoding collagen t ypes I , I I, I X a nd X , a graman, n on-codon p rotein CILP, proinflammatory cytokines (interleukin 1 and 6), matrix metalloproteinase-3. Polymorphism of the genes of the receptors of vitamin D, as well as its role in the development of degenerative disorders in the intervertebral disc are actively researched. The molecular profile of intervertebral disc herniationis a correlation between proinflammatory cytokines, growth factors and other molecules that are expressed by cells, affecting the nerve roots and accompanied by pain syndrome.